301 WOUND FLUID GLYCOSAMINOGLYCANS AND THEIR INFLUENCE ON CELL BEHAVIOR DURING WOUND REPAIR. (1st January 2006) - Na, C.; Taylor, K.; Trowbridge, J.; Gallo, R.
Abstract : Introduction: Epithelial wound healing consists of a variety of steps resulting in the repair of the skin following injury. One important aspect of wound healing is new tissue formation that involves cell proliferation stimulated by fibroblast growth factors (FGFs) and inflammation initiated by the release of cytokines. During wound repair, the surrounding fluid contains high concentrations of linear glycosaminoglycan chains, specifically dermatan sulfate and hyaluronan. Dermatan sulfate has been shown to be an important cofactor for FGF-2 and FGF-7, both of which are essential components of wound repair. The purpose of this study was to test the hypothesis that soluble dermatan sulfate and hyaluronan in wound fluid serve as important elements in the repair process, enabling epithelial growth and modifying the inflammatory response. Methods: To test the effect of glycosaminoglycans on cell proliferation and migration, we used a model of artificial wounding based on migrating keratinocytes in culture. In addition, we explored the inflammatory aspect of wound healing by introducing glycosaminoglycans to macrophages to quantify the release of proinflammatory cytokines. The mechanism of glycosaminoglycan action was explored by using a cell model in which cell membrane fluidity was perturbed by naturally occurring membrane-active peptides. Results: The introduction of exogenous dermatan sulfate to cultured keratinocytes in vitro impaired the ability of cells to migrate and proliferate into an open space. A mixture of wound fluid glycosaminoglycans induced the release of proinflammatory cytokines from macrophages. To determine which GAG present in wound fluid induced cytokine release, several glycosaminoglycans, including dermatan sulfate, heparan sulfate, and hyaluronan, were tested for their ability to activate macrophages. It was determined that hyaluronan is capable of inducing cytokine release, whereas the other glycosaminoglycans are not. The effects of hyaluronan stimulation are dependent on membrane fluidity because treatment of cells with LL-37, which disrupts membrane fluidity, abrogated the inflammatory response. Conclusions: We conclude that wound fluid glycosaminoglycans participate in several roles critical to wound healing. This study has further elucidated the molecular basis of wound repair by defining dermatan sulfate as a critical regulator that can influence the function of growth factors necessary for angiogenesis, epidermal proliferation, and cell growth.